Atomistic-continuum hybrid simulations for compressible gas flow in a parallel nanochannel. (May 2017) - Zhou, Wen-Jing; Yu, Zhi-Qiang; Li, Zhong-Zhen; Wei, Jin-Jia; Tao, Wen-Quan
Highlights: An atomistic-continuum hybrid method is developed for compressible gas flow. The correct velocity and pressure profiles are produced. A linear relationship between slip length and Knudsen number is obtained. The possible reasons for deviation from the Maxwell model are explained. Abstract: An atomistic-continuum hybrid method is proposed to simulate the compressible gas flow in nanochannel. Based on the domain decomposition method, the computational region is divided into two parts: the atomistic part and the continuum part. In the region near the wall, the molecular dynamics (MD) simulation is used; in the bulk region, finite volume method (FVM) is employed, which also provides necessary information for constructing inlet and outlet boundary conditions of atomistic part. After some validation of the hybrid code, it is used to study the Poiseuille flow in nano-scale channel. Pressures at the inlet and outlet boundaries are both generated as expected, and the pressure gradient is induced along the channel. The velocity and pressure profiles from the hybrid method agree well with full MD simulation. The variations of slip velocity and dimensionless slip length with Knudsen number are also studied, and a linear equation between dimensionless slip length and Knudsen number is obtained.